Complete math review for the pharmacy technician - Hopkins, Jr., William A. (Washington, D.C : American Pharmacists Association, 2010)
Complete Math Review for the Pharmacy Technician is a friendly, self-instructional approach to lifelong understanding of pharmacy calculations.
Back to basics -- Systems of measurement -- Ratio and proportion -- Interpreting drug orders and calculating doses -- Reducing and enlarging formulas and compounding -- Reconstitution of dry powders -- Intravenous flow rates -- Percentage calculations -- Concentrations and dilutions -- Electrolyte solutions -- Temperature conversions -- Business math -- Medication errors and clinical challenges
Includes index.
Keywords: PHARMACEUTICAL ARITHMETIC